High prevalence of persistent emotional distress in desmoid tumor. Issue 2 (10th December 2019) - Ingley, Katrina M.; Klein, Roberta; Theobalds, Nicole; Burtenshaw, Sally; Abdul Razak, Albiruni R.; Chen, Bo; Xu, Wei; Gladdy, Rebecca; Li, Madeline; Gupta, Abha A.
Abstract: Objective: Clinical experience suggests a high prevalence of emotional distress in patients with desmoid tumor (DT). We examine longitudinal Distress Assessment and Response Tool (DART) scores to estimate prevalence and persistence of distress, and compare cross‐sectional data between DT and malignant sarcoma cohorts, to identify predictors of distress. Methods: Patients with DT completed DART at: T1—diagnosis, T2—during, T3—<6 months, and T4—≥6 months, post‐treatment. DART includes patient‐reported outcome measures of physical symptoms (ESAS‐r), depression (PHQ‐9), anxiety (GAD‐7), and social difficulties (SDI‐21). Descriptive prevalence and persistence of anxiety, depression, and wellbeing are reported, and mixed model regression analyses determine predictors of distress. Results: Between 2012 and 2018, a total of 152 DART screens from 94 patients with DT were completed (T1: n = 44, T2: n = 31, T3: n = 22, T4: n = 55). Patients had a mean age 40 years, 78% were female and DT locations were abdominal wall (48%), extremity (30%), and mesentery (22%). Moderate to severe ESAS‐r scores (≥4) persisted at T4 for anxiety (20%), depression (13%), and poor wellbeing (31%). Compared to 402 patients with malignant sarcoma, patients with abdominal wall sited DT reported severe PHQ‐9 and GAD‐7 scores twice as frequently. Abdominal wall location, female sex, history of mood problems, and psychosocial concerns were significant predictors of anxiety, depression, and poor wellbeing in DT. Conclusions: Adults with DT experience persistently high emotional distress compared to patients with malignant sarcoma. Women with abdominal wall DT, prior mood, and current psychosocial concerns need early attention within multidisciplinary treatment settings to reduce persistent distress.